NAMA-NAMA PANGGILAN DALAM BAHASA INGGRIS DAN BAHASA MONGONDOW (SUATU ANALISIS KONTRASTIF) - Manurip, Sintia; Lasut, Theresia M.C; Pelealu, Hetty (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACT The study is an attempt to describe and analyze the nicknames in English and Mongondow language. The objectives of the research are to identify, classify, and to analyze the kinds and the meanings of the nicknames in English and Mongondow language based on its category then to contrast them. Hence, the similarities and differences of nicknames can be found in both languages. The concept of the nicknames used in this research has been adopted from Hickerson and Przecha’s concepts. Observation participation method is used in this research by interacting with people in Maelang who speak Mongondow Language. The English data have been collected from English textbook and website. Theoretically, this research can enrich the knowledge in terms of etnholinguistic study, especially about nicknames in English and Mongondow language. Practically, this research can give information and motivate the readers in identifying the nicknames of other languages. The result shows that the nicknames in English and Mongondow language have similarities in terms of nicknames in related to (1) name is a virtue, (2) surnames as given names, (3) surnames as nicknames, (4) baptismal names. Besides, these two languages have also connotational and associational meaning.————————————–Keywords : Nicknames, English and Mongondow Language, Contrastive Analysis.